Distinct serum steroid profiles between adrenal Cushing syndrome and Cushing disease - Gao, Chang; Ding, Li; Zhang, Xiaona; Yuan, Menghua; Tang, Shaofang; Li, Wei; Ye, Yuanyuan; Liu, Ming; He, Qing (Frontiers in Endocrinology, 2023)
Background: Differentiating between adrenal Cushing syndrome (adrenal CS) and Cushing disease (CD) can be challenging in case of equivocal of falsely elevated adrenocorticotropic hormone (ACTH) values. We aim to investigate the diagnostic value of serum steroid profiles in differentiating adrenal CS from CD. Method: A total of 11 serum steroids in adrenal CS (n=13) and CD (n=15) were analyzed by liquid chromatography with tandem mass spectrometry (LC-MS/MS). Age- and gender- specific steroid ratios were generated by dividing the actual steroid concentration by the upper limit of the respective reference range. Principal component analysis (PCA) and orthogonal partial least squares discriminant analysis (OPLS-DA) were performed. Results: PCA and OPLS-DA analysis showed distinct serum steroid profiles between adrenal CS and CD. Dehydroepiandrosterone sulfate (DHEA-S), dehydroepiandrosterone (DHEA) and androstenedione ratios were identified as biomarkers for discrimination by variable importance in the projection (VIP) in combination with T test. The sensitivity and specificity of DHEA-S ratio <0.40 were 92.31% (95%CI: 64.0% - 99.8%) and 93.33% (95%CI: 68.1% - 99.8%) in identifying adrenal CS. The sensitivity and specificity of DHEA ratio <0.18 were 100% (95%CI: 75.3%- 100.0%) and 100% (95%CI: 78.2%- 100.0%) in identifying adrenal CS. Conclusion: Our data support the clinical use of DHEA-S ratio and DHEA ratio in the differential diagnosis of adrenal CS and CD, especially when falsely elevated ACTH is suspected.